(untitled) (Research, Society and Development, 2023)
The process of preparing school lunches requires compliance with sanitary measures established by the National Health Surveillance Agency – ANVISA. In this context, this study aimed to identify the physical and hygienic-sanitary conditions of the kitchens where these foods are prepared, in child education units of the municipal public system of Santarém-PA. Data collection was carried out through an in loco survey in the kitchens of the units, covering both a verification of the physical and hygienic-sanitary conditions of the place and an interview with the food handlers, in order to inquire about sociodemographic and social issues. about the food handling process. To verify the environment, a checklist adapted from Almeida (2013) was used, where spaces were divided into blocks, namely: block A – buildings and facilities in the food preparation area; block B – handlers; block C – processes and procedures and block D – hygiene and environment. As main results, it was identified that 100% of the units participating in the research showed non-compliance with regard to the determinations of the current legislation for the hygienic-sanitary conditions in the preparation of food, referring to the facilities, processes and procedures related to the area of food preparation, as well as the storage conditions of products used by professionals who prepare food.